National Parks in Iran and the Evolution of People-Park Relationships. Issue 6 (November 2016) - Amanat, Abbas; Tahbaz, Morad; Bayani, Niloufar; Cole, Camille; Seyed-Emami, Kavous; Ashayeri, Sheyda
Abstract : In Iran, national parks were originally created to protect wildlife and natural expanses. Over time, the exigencies of handling conflict with the locals and a worldwide shift in management approaches from strict protection to newer participatory approaches led Iranian conservationists to adopt the discourse of participatory conservation. However, serious institutional and attitudinal obstacles have prevented policy makers and officials from developing good relations with local communities, making it difficult to serve the interests of conservation or accommodate tourists. Based on interviews with past and present officials of the Department of the Environment of Iran and other field observers, this paper discusses approaches to conservation that reconcile the requirements of conservation with the needs of the people who benefit from reserves.